Bio-literacy perspective: A study of the implementation of outdoor learning-based science process skills in plant introduction - Diana Hernawati; Dina Maulina; Rita Fitriani; Rinaldy Rizal Putra (Universitas Ahmad Dahlan, 2020)
The study aims to describe an implementation study of outdoor learning based science process skills based on a bio-literacy perspective. The method used is quantitative analysis to see the influence of implementation of science process skills, while to reveal the effect of each indicator of each predictor used qualitative descriptive analysis. The samples in this study were two groups of biology teacher candidates taken by cluster random sampling techniques. The research instrument is a science process skills test with data analysis techniques using Anacova. The results concluded simultaneously there was an influence on the implementation of the science process-based outdoor learning skills from the perspective of bio-literacy at a level of significance 0.05. To measure the ability of bio-literation, it is not only needed instruments at the level of conceptual understanding but instruments that can assess learning with scientific methods and practices. Practically science process skills can be an effort in mapping the domain of biological literacy.